Religious Commitment and Gratitude as a Strategy for Promoting Student Mental Health - Sholichatun, Yulia; Mangestuti, Retno; Suryani, Suryani; Huroniyah, Fuadatul; Marwing, Arman (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Despite global students' mental health problems being prevalent, adequate attention and resources to treat mental health problems are still lacking. Meanwhile, several studies found that religious commitment and gratitude can play an essential role in addressing the issue of mental health problems. This study explored religious commitment to promote mental health and gratitude as moderating variables to address this gap. This study used the Brief Scale of Mental Health 12, the General Mental Health Questionnaire (GHQ-12), the Gratitude Resentment and Appreciation Test (GRAT), and the Religious Commitment Inventory (RCI–10) scales. Data were taken from 320 students of four state Islamic Universities in East Java, Indonesia. This study utilized descriptive and regression analysis techniques. The result of the data analysis demonstrated three main findings as follows. First, the students had a high level of mental health. Second, religious commitment positively affected mental health. Third, gratitude could become a variable that strengthens the relationship between religious commitment and mental health. Research implication in education is attempting to improve mental health among students not merely on the religious commitment but also on emphasizing systematic ways to develop gratitude in students' daily lives as a moderator that plays a role in maintaining the relationship between mental health and religious commitment. This study was based solely on a quantitative approach; therefore, a mixed-method model is recommended for further investigation to understand the process of improving mental health through religious commitment and students' gratitude better.